The effects of ultrasonic vibration on Portevin–Le Chatelier (PLC) effect and stress-strain behavior in aluminum alloy 2024. (February 2023) - Kang, Jiarui; Liu, Xun; Wang, Tianzhao
Abstract: The effect of ultrasonic vibration on the stress-strain behavior and the Portevin–Le Chatelier (PLC) effect in aluminum alloy 2024 O temper and T4 were investigated based on ultrasonically assisted micro-tensile tests. Flow stress in both heat treatments was found to be decreasing when ultrasonic vibration is applied. A higher percentage of stress reduction and the residual softening effect was observed in O temper. High-speed digital image correlation reveals the enhanced PLC bands in both heat treatments. While no PLC band was observed in T4 originally, clear PLC bands appear with applied ultrasound. Spatio-temporal analysis revealed that in both O temper and T4 conditions, the critical strain of the PLC effect decreases under ultrasonic vibration. In addition, a higher strain rate magnitude was observed in conditions with ultrasonic vibration. Graphical abstract: Image, graphical abstract